Eurasian land routes and the development of hesychast psycho-physiological techniques in the thirteenth Century:: New Perspectives on Byzantine Orthodoxy and the Global Middle Ages - KYRIACOU, Chrysovalantis (Byzantina Symmeikta, 2025)
Mādhavacandra’s Amṛtasiddhi, the earliest Yoga manual in Sanskrit, was probably composed in the Deccan Plateau of Southern India sometime during the second half of the eleventh century CE and certainly before 1160. The thirteenth century marked the transmission of meditative techniques focusing on breathing control, through the Ilkhanate in Central Asia and Anatolia. The Islamisation of Amṛtakuṇḍa seems to have been instrumental in appropriating Hindu-Buddhist techniques in Sufism and Kabbalah. The aim of the article is to explore the journey of meditative wisdom and technique from Southeastern Asia to the Mediterranean, attempting to reconstruct possible routes and the influence of meditative techniques on the pre-existing --but dynamically reshaped during the thirteenth and fourteenth centuries-- tradition of Hesychasm in Asia Minor and Mount Athos. The article closes with a number of desiderata for future research.